The role of leadership functions and organizational culture improving employee performance - Zuchri Abdussamad (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2017)
This study aims to analyze the influence of leadership functions and organizational culture on the performance of academic employees at the University of Ichsan Gorontalo simultaneously or partially. The method of analysis used is multiple linear regressions. This research uses purposive sampling and data collection techniques using questionnaires. The results showed that leadership functions significantly affect employee performance. Organizational culture has a significant effect on employee performance. Leadership function and organizational culture have simultaneous effect on employee performance.